Rediseño de planta de sales mineralizadas (1994)
The study began with general aspects of mineralized salt, its importance in animal feed, its components, minimum requirements, existing formulations, and the product's characteristics and composition. Once the problem was stated, a market study was required to analyze the historical behavior of demand for mineralized salt and the livestock population that consumes it. Based on this data, the potential demand or demand for the project was determined, which corresponds to 45% of the total unmet demand.